Effect of Yoga on Vital Physiological Indicators and Mental Health among Undergraduate Medical Students - Khadka, Pratiksha; Mishal, Jyoti (Nepal Journal of Health Sciences, 2025)
Introduction: Yoga is an ancient practice originating from India that has been potentially used to improve physical, mental, and spiritual health. The long-term effects of the practice of yoga are evident; however, the immediate impact of yoga is not very well established, particularly among the population with high academic stress, like medical students. Objective: To investigates the physiological and psychological impacts of a 12 week yoga and meditation program on undergraduate medical students at Madan Bhandari Academy of Health Sciences. Methods: By employing cross-sectional analytical design, the target population of 80 students were grouped into the yoga group and the control group. The pretest and post test data of yoga group on the key health indicators, including the pulse rate, systolic and diastolic blood pressure on the student’s health profile, were taken before and after the student underwent the intervention. The Sahaja yoga technique was a pplied in the intervention. Result: The results revealed significant reductions in heart rate (15.53%) and blood pressure (Systolic blood pressure by 6.12% and Diastolic blood pressure by 13.25%) in the yoga group compared to the control group (4.43% HR, +1.84% Systolic blood pressure, and 2.13% Diastolic blood pressure, all p < 0.001), alongside improvements in perceived stress and anxiety levels. Conclusion: The study concludes that a 12-week yoga and meditation program significantly improved both physiological parameters and psychological wellbeing in undergraduate medical students.